(untitled) (Marketing Journal, 2025)
This article explores the advantages of dual education for higher education institutions and addresses issues related to the innovative implementation of dual education within the higher education system, as well as its practical application. Additionally, the paper presents a scheme for organizing dual education in higher education institutions.